- Picture Word Inductive Model (PWIM) : Assisting Students in Improving Their Writing Ability of Procedure Text - Sulhah, Siti Sulhah; Yayu Heryatun; Fadilla Oktaviana (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
The aims of this study are to know how to implement PWIM and also to find out whether the writing ability of procedure texts can be improved through PWIM. This study employed the classroom action research design, which was carried out in three cycles. This study included 25 ninth-grade students of MTs. Daarul Ulum Panyaungan in the academic year 2023-2024. Data for this study were collected through tests, diary notes, observation sheets, and questionnaires. The findings of the investigation suggest that, when employing PWIM, the teacher used eight phases that comprise: selecting an image; recognizing an image; labeling an image; reading and reviewing the picture word chart; adding words to the picture word chart; leading students to create a title; asking students to generate a sentence; and reviewing the sentence. The next finding showed that students’ scores improve from pre-research to the test. The students’ mean in test 1 was 57.8%, in test 2 was 63.4%, and in test 3 was 72.4%. Furthermore, based on diary notes, observation sheets, and questionnaire sheets, it was discovered that the teaching-learning process worked successfully. The study concludes that using PWIM as a learning medium increases students' capacity to produce procedure texts.